2009
DOI: 10.1105/tpc.108.063719
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Elevation of Cell Wall Invertase Activity by Silencing Its Inhibitor in Tomato Delays Leaf Senescence and Increases Seed Weight and Fruit Hexose Level  

Abstract: Invertase plays multiple pivotal roles in plant development. Thus, its activity must be tightly regulated in vivo. Emerging evidence suggests that a group of small proteins that inhibit invertase activity in vitro appears to exist in a wide variety of plants. However, little is known regarding their roles in planta. Here, we examined the function of INVINH1, a putative invertase inhibitor, in tomato (Solanum lycopersicum). Expression of a INVINH1:green fluorescent protein fusion revealed its apoplasmic localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
295
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 269 publications
(340 citation statements)
references
References 64 publications
22
295
0
2
Order By: Relevance
“…Consistently, high CWIN activities correlate with high Glc level and mitotic activity in faba bean embryo (Weber et al, 1996(Weber et al, , 1997 and maize endosperm (Cheng et al, 1996;Vilhar et al, 2002). Loss of CWIN expression reduces seed filling in maize (Cheng et al, 1996) and rice , whereas elevation of CWIN activity by silencing its inhibitor increases seed size in tomato (Jin et al, 2009), demonstrating the critical role of CWIN in seed development.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Consistently, high CWIN activities correlate with high Glc level and mitotic activity in faba bean embryo (Weber et al, 1996(Weber et al, , 1997 and maize endosperm (Cheng et al, 1996;Vilhar et al, 2002). Loss of CWIN expression reduces seed filling in maize (Cheng et al, 1996) and rice , whereas elevation of CWIN activity by silencing its inhibitor increases seed size in tomato (Jin et al, 2009), demonstrating the critical role of CWIN in seed development.…”
mentioning
confidence: 70%
“…Extensive studies have shown essential roles of CWIN in seed filling, probably through regulating Suc unloading and the establishment and maintenance of sink strength (Cheng et al, 1996;Weber et al, 1996;Wang et al, 2008;Jin et al, 2009;Zanor et al, 2009). However, it remains largely unknown how CWIN exerts its regulation early in seed development .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tomato flowers the LIN5-dependent generation of hexoses (Zanor et al, 2009) is regulated posttranslationally by a LIN5-specific inhibitor protein INVINH1, which gene is coexpressed with LIN5 within the gynoecia (Jin et al, 2009). Silencing of INVINH1 allowed extra invertase activity that led to more hexoses being available for developing seeds and was followed by an increase in seed weight and size (Jin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of INVINH1 allowed extra invertase activity that led to more hexoses being available for developing seeds and was followed by an increase in seed weight and size (Jin et al, 2009). Interestingly, such invertase inhibitors are downregulated by OPDA (Taki et al, 2005).…”
Section: Discussionmentioning
confidence: 99%